Experimental Investigation of Bearing Capacity of Screw Piles and Excess Porewater Pressure in Soft Clay under Static Axial Loading - Karkush Mahdi O. (EDP Sciences, 2021)
In this study, the behavior of screw piles models with continuous helix was studied by conducting laboratory experimental tests on a single screw pile that has several aspect ratios (L/D) under the influence of static axial compression loads. The screw piles were inserted in a soft soil that has a unit weight of 18.72 kN/m3 and moisture content of 30.19%. Also, the soil has a liquid limit of 55% and a plasticity index of 32%. A physical laboratory model was designed to investigate the ultimate compression capacity of the screw pile and measure the generated porewater pressure during the loading process. The bedding soil was prepared according to the field unit weight and moisture content and the failure load was assumed corresponding to a settlement equals 20% of helix diameter. The ultimate compression capacity of screw piles higher than the ultimate capacity of ordinary piles and the ultimate compression capacity increases with decreasing the aspect ratio. The ultimate bearing capacity of the flexible screw pile (L/D<20) is greater than the ordinary pile by 59.5% and with the rigid screw pile (L/D>20), the ultimate bearing capacity could reach 250% compared with the ordinary pile. Also, the estimated ultimate compression capacity of flexible screw piles well agreed with those measured experimentally, but a large difference was noted for rigid screw piles.